A T‐Junction Dual Nanopore for Single Nanoparticle Analysis. Issue 4 (28th October 2021) - Liao, Caizhi; Antaw, Fiach; Wuethrich, Alain; Trau, Matt
Abstract : Label‐free detection methods such as resistive pulse sensing (RPS) have become a pivotal platform for the characterizations of nanoscale objects, providing real‐time monitoring and single‐molecule resolution. Major challenges for RPS platforms include the short translocation time of nanoscale objects passing through the pore and limited dynamic range due to the need for particle sizes to be within 10−90% of the pore size. These issues severely limit the fidelity of the measured signals, particularly when measuring unknown samples. Herein, a T‐junction‐shaped dual pore system that slows down the motion of translocating nanoparticles is proposed, and that allows particle translocations to be unambiguously allocated to one of the two pore structures. Moreover, because the two pore structures are of different sizes, the size range of particles that may be measured without clogging is increased. The prepared dual pores afford to measure the size features and surface charge properties of nanoparticles with high accuracy. Importantly, the dual‐pore system enables the study of the dynamic motion behaviors of adjacent nanoparticles. The application of these dual pores for characterizing the protein corona of bioparticles is exemplified. Abstract : A fabrication strategy based on focused ion beam milling of a nanopipette is reported to prepare a T‐junction dual nanopore for resistive pulse sensing.